A combination containing natural extracts of clove, Sophora flower bud, and yam improves fertility in aged female mice via multiple mechanisms - Liu, Wei; Wang, Xinyu; Chen, Yating; Zhang, Huiyu; Chen, Jing; Zhang, Jing; Wu, Tinghe; Li, Jing (Frontiers in Endocrinology, 2022)
With society development, the age at which women choose to have children has been gradually delayed. To improve the reduced fertility in women at advanced maternal age, we developed a healthy product that contains natural extracts from clove, Sophora flower bud and Chinese yam, named DACHAO. In this study, we aimed to investigate its effects on the ovarian functions in aged mice. Using MitoTracker probes, ROS, and JC-1 staining, we found that the administration of DACHAO improved mitochondria functions in aged oocytes. Increased blastocyst formation was also observed in DACHAO-treated oocytes, accompanied with increased cell numbers and decreased apoptosis in blastocysts. Fertility tests showed the DACHAO-treated mice had a greater first litter size. Further study revealed that the DACHAO treatment could alleviate the retarded ovarian function in aged mice via changes in serum hormone levels, over-expression of antioxidant factors, under-expression of inflammation-related factors, and reduced apoptosis in the ovaries.